Synthesis of nitrogen-doped ZnO nanoparticles by RF thermal plasma. (April 2016) - Hiragino, Yuto; Tanaka, Toshimi; Takeuchi, Hiroshi; Takeuchi, Akira; Lin, Jie; Yoshida, Toshiyuki; Fujita, Yasuhisa
Graphical abstract: Photograph of RF plasma torch and RF thermal plasma generated by oxygen and argon discharge. Abstract: The nitrogen-doped ZnO nanoparticles (NPs) were successfully synthesized by using an RF thermal plasma process which would be a promising technique to the massive production. XRD measurements revealed that the formation of the hexagonal ZnO wurtzite structure. The synthesized nitrogen-doped ZnO NPs showed the nitrogen and carbon concentrations of 3.1–4.6 × 10 20  cm −3 and 1.1–1.2 × 10 20  cm −3 . The hole injection was confirmed by evaluating band edge electroluminescence from the LED structures using nitrogen doped ZnO NPs as a p-type layer.